2016
DOI: 10.18632/oncotarget.8171
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum fibrinogen is an independent prognostic factor in operable esophageal cancer

Abstract: In order to fully elucidate the association between serum fibrinogen and prognosis of esophageal cancer, we examined serum fibrinogen concentrations in 1512 patients who underwent esophagectomy by the Clauss method. The impact of fibrinogen on overall survival and disease-free survival was analyzed using the Kaplan-Meier method and Cox proportional hazard models. Hyperfibrinogenemia was significantly associated with older age, male gender, smoking, alcohol consumption, weight loss, advanced pathological T stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
6
24
1
Order By: Relevance
“…We identified consecutive patients with esophageal cancer who underwent surgical resection at Sun Yat-sen University Cancer Center (Guangzhou, China) between December 2000 and December 2008 (17,18). All patients were newly confirmed to have esophageal cancer and had not received treatment.…”
Section: Patient Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified consecutive patients with esophageal cancer who underwent surgical resection at Sun Yat-sen University Cancer Center (Guangzhou, China) between December 2000 and December 2008 (17,18). All patients were newly confirmed to have esophageal cancer and had not received treatment.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Patients were excluded on the basis of the following criteria: history of other cancer; prior neoadjuvant therapy; died in the perioperative period; lack of information on HBV infection or hepatitis viral infections other than HBV. Esophagectomy and pathologic stage was described in our previous study (17,18). All patients provided written informed consent for their information to be stored and used in the hospital database.…”
Section: Patient Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[98][99][100] Hyperfibrinogenemia is increasingly recognized as an important risk factor influencing cancer development and outcome, associated with poor prognosis in various cancers (e.g., ovarian, biliary, esophageal, and pancreatic). 26,[101][102][103][104][105][106] Globally, an elevated content of FBG in plasma before treatment significantly correlates with decreased survival in patients with solid tumors. 107 Recently, in rectal cancer tissues, Repetto et al 108 identified FBG ␤ chain as a marker for identification of poor responders before therapy.…”
mentioning
confidence: 99%